Lithuanians in Michigan - Grazulis, Marius K. (Discovering the peoples of Michigan., 2009)
From the Publisher: Lithuanians in Michigan recounts the history of an immigrant group that has struggled to maintain its identity. Grazulis estimates that about 20 percent of the 1.6 million Lithuanians who immigrated to the United States arrived on American shores between 1860 and 1918.